2021
DOI: 10.3390/ijms22179175
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Analysis of GmLACS2-3 Reveals Its Involvement in Cutin and Suberin Biosynthesis along with Abiotic Stress Tolerance

Abstract: Cutin and wax are the main precursors of the cuticle that covers the aerial parts of plants and provide protection against biotic and abiotic stresses. Long-chain acyl-CoA synthetases (LACSs) play diversified roles in the synthesis of cutin, wax, and triacylglycerol (TAG). Most of the information concerned with LACS functions is obtained from model plants, whereas the roles of LACS genes in Glycine max are less known. Here, we have identified 19 LACS genes in Glycine max, an important crop plant, and further f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 33 publications
1
45
0
1
Order By: Relevance
“…The degree of law varies with different stresses, plants, and genes, indicating that the response of StPAL genes to high temperature, drought, and MEJA was different. This similar expression difference also exists in the GmLACS gene, and the GmLACS studied by Asma Ayaz et al (2021) also showed different expression patterns under other stress treatments [ 42 ]. This gene expression difference is also advantageous.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The degree of law varies with different stresses, plants, and genes, indicating that the response of StPAL genes to high temperature, drought, and MEJA was different. This similar expression difference also exists in the GmLACS gene, and the GmLACS studied by Asma Ayaz et al (2021) also showed different expression patterns under other stress treatments [ 42 ]. This gene expression difference is also advantageous.…”
Section: Discussionmentioning
confidence: 65%
“…Different plants contain different numbers of PAL genes, and the size of the genome and gene duplication events cause these differences [ 41 ]. The LACS gene family also has other gene numbers in various plants [ 42 ]. Additionally, there are more tandemly duplicated genes in the StPALs, which confirms this.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the prime editing system has sufficient versatility to complete specific forms of genome editing, these new developments have considerable potential. Moreover, it can be modified for different purposes (including crop production, resistance to abiotic and biotic stresses, and crop plant quality improvement; Yasmin et al, 2020 ; Ayaz et al, 2021a ). Moreover, the Cas12b (C2c1) system has recently been successfully applied for editing genomes in cotton plants to enhance the resistance to high temperatures, thereby paving the way for the development of varieties that can be cultivated under heat stress conditions ( Wang et al, 2020 ).…”
Section: Zfn Talen and Crispr-cas Genome-editing Techniquesmentioning
confidence: 99%
“…Over the last few decades, genome sequencing, combined with rapid advancement in bioinformatics has led to comprehensive molecular studies on the model plants as well as non-model plants with economic importance. Furthermore, the application of bioinformatics can be used to elucidate the complex biological processes generated from molecular datasets that would unravel hypotheses of the gene’s functions, protein interactions, and other molecular mechanisms efficiently [ 47 , 48 , 49 ]. However, public databases host inaccurate information on the putative roles of TPs due to various limitations in the gene- and protein-sequence annotation processes and erroneous mismatching between genomic and functional data on protein function.…”
Section: Introductionmentioning
confidence: 99%